2019
DOI: 10.1101/627398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenome-wide Mendelian randomization mapping the influence of the plasma proteome on complex diseases

Abstract: The human proteome is a major source of therapeutic targets. Recent genetic association analyses of the plasma proteome enable systematic evaluation of the causal consequences of variation in plasma protein levels. Here, we estimated the effects of 1002 proteins on 225 phenotypes using two-sample Mendelian randomization (MR) and colocalization. Of 413 associations supported by evidence from MR, 130 (31.5%) were not supported by results of colocalization analyses, suggesting that genetic confounding due to link… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 92 publications
(111 reference statements)
2
88
0
Order By: Relevance
“…We also found genetic evidence that selected protein targets, such as for MARK3 and monocyte count, have potential for adverse effects on other health outcomes, but note that this was not a general characteristic of all tested 'druggable' targets. Further, in-depth characterization of the targets identified will be required as a first step in gauging the likely success of any new or repurposed drugs identified via this analysis 33 .…”
Section: A Variant At the Abo Locus Links Susceptibility Of Respiratomentioning
confidence: 99%
“…We also found genetic evidence that selected protein targets, such as for MARK3 and monocyte count, have potential for adverse effects on other health outcomes, but note that this was not a general characteristic of all tested 'druggable' targets. Further, in-depth characterization of the targets identified will be required as a first step in gauging the likely success of any new or repurposed drugs identified via this analysis 33 .…”
Section: A Variant At the Abo Locus Links Susceptibility Of Respiratomentioning
confidence: 99%
“…Understanding which proteins influence which diseases is a fundamental problem in biomedical science since proteins are the major biological effector molecules. Proteins are also the targets of most medicines, so interest has emerged in the use of MR approaches to identify and validate drug targets [21][22][23][24] . Moreover, recent technological developments enable measurement of hundreds or thousands of proteins on an -omics scale in a single biological sample 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The Ensembl 97 GRCh38 human genome assembly contains an estimated 20,454 protein coding genes, encoding an estimated 24,700 protein coding transcripts (merged Ensembl/Havana annotation). Of these transcripts,21,869 have a support level of ≤ 2, meaning that there is some level of experimental support for the presence of these transcripts. In addition, UniProt (version 2019_06, combining SwissProt and TrEMBL) reports 20,416 high quality manually annotated proteins.…”
mentioning
confidence: 99%
“…In addition, protein coding variants may cause technical artifacts in both affinity proteomics and mass spectrometry 43,44 . However, systematic conditional and colocalization analyses in causality testing using the aptamer-based technology have shown that pQTLs driven by common missense variants being artefactual is an unlikely event 11,45 .…”
Section: Figure 2bmentioning
confidence: 99%